SOURCES OF STRESS AND WELL-BEING IN DENTAL STUDENTS - Cristina Teodora Preoteasa; Gabriel Mircescu; Mona Corina Buzea; Elena Preoteasa (Romanian Society of Oral Rehabilitation, 2015)
Introduction: Psychological well-being is an important health component, which influences the ability to learn and achieve the maximum professional potential. The aim of this study was to identify the sources of stress and assess well-being in dental students. Materials and methods: Am observational study was implemented on a convenience sample of 2nd and 3rd year dental students, from "Carol Davila" University of Medicine and Pharmacy, Bucharest, Romania. There was collected data upon sources of stress, by the usage of a modified version of Dental Environment Stress (DES) questionnaire, and psychological well-being assessed by WHOFive Well-being Index. Results: The identified primary sources of stress perceived by the dental students were competition for grades, examinations, lack of time for relaxation, expectation versus reality of dental school and shortage of allocated clinical time. From the domains of DES questionnaire, most stressful were perceived those related to academic factors, respectively in descending order: the "academic work", "clinical factors" and "educational environment". By multiple regression analysis there was observed that only stressors of "education environment" domain significantly predicts dental student' psychological well-being. Conclusion: Future research is recommended in order to identify the best approaches for the implementation of education in dental schools.